2004
DOI: 10.1111/j.1365-2591.2004.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between two electronic apex locators: an in vivo investigation

Abstract: Under the five different clinical situations both EALs revealed accurate measurements. Apex Finder was negatively influenced by NaOCl in the root canal. The Root ZX was more frequently unable to reveal stable measurements in low conductivity canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 37 publications
7
53
1
7
Order By: Relevance
“…Some previous studies have demonstrated that EAFLs gave incorrect results in teeth with wide foramina (24,25,34). Huang (25) concluded that the operation of an EAFL was based on the principles of electricity rather than the biological properties of the tissue involved.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some previous studies have demonstrated that EAFLs gave incorrect results in teeth with wide foramina (24,25,34). Huang (25) concluded that the operation of an EAFL was based on the principles of electricity rather than the biological properties of the tissue involved.…”
Section: Discussionmentioning
confidence: 97%
“…The foramen on the root surface is an appropriate reference because it is easily visualized under the microscope (34,35), and a well-defined apical constriction is not expected in root canals of teeth with apical lesions (6,7,9). Moreover, it has been shown that the use of the Root ZX meter's reading of APEX gave more accurate measurements than the 0.5 bar reading (35,36).…”
Section: Discussionmentioning
confidence: 97%
“…Dentre essas, o algina-(o canal foi irrigado) pode ter feito com que o circuito fechasse anteriormente a posição do forame 22 . Quanto à análise da precisão dos localizadores eletrônicos em diferentes grupos de dentes, no caso dentes unirradiculares incisivos, caninos e pré--molares, também não se registrou diferenças estatísticas significantes entre esses para nenhum dos localizadores, sendo o resultado semelhante ao de estudos anteriormente realizados 23,24 . Avaliando-se a precisão dos localizadores, a literatura considera que quando os dentes são obturados no limite entre 0,0 e 2,0 mm aquém do ápice dentário apresentam 94% de sucesso 25 .…”
Section: Discussionunclassified
“…17 This report of five cases shows that, under certain conditions, it is possible to perform root canal treatment using electronic conductometry without transoperative radiographic verification. When compared to other radiographic methods used to determine the working length, 10,20,21 electronic apex locators yield similar or even higher and more accurate 8,22,23,24,25,26 results for conductometry. One reason why the working length determined by means of radiographic methods may be imprecise is because it is based on the interpretation of twodimensional images of a threedimensional object, in which the radiographic apex is considered the limit, whereas in the electronic method, the reference point is the apical foramen which is radiographically imperceptible.…”
Section: Discussionmentioning
confidence: 99%